Qualitative and Quantitative Study of Older Japanese, German, Brazilian and US Air Travelers---the BEST AGE study. (September 2014) - McMullin, Dianne; Angerer, James; Green, Rush; Stancato, Fernando; Ciaccia, Flavia; Cintra, Aristides; David, Alexandre; Morgan, Embraer Donald; Mastaw, Melody; Ruggiero, Frank
Increases in air travel, disposable income, and median age around the world suggest that the needs of the older traveler will have an increasing impact on the air travel system. Embraer, Boeing and GMA Research, Inc. conducted focus groups, fly-along ethnographic observations and on-line surveys with older air travelers in Japan, Germany, Brazil and the United States. Difficulties walking long distances, accessing overhead bins, operating automated check-in kiosks and in-flight entertainment systems, and entering and exiting seats were common themes. The relatively limited space and perceived sanitary conditions within the lavatories also posed limitations for many older travelers. However, a striking number of older travelers report a desire to continue travelling as often or more frequently in the future.